Penguatan Sanksi Tindakan Terhadap Anak Pelaku Kekerasan Seksual melalui Model Parenting Order - Cahyaningrum, Nadya; Endrawati, Lucky; Maharani, Febrianika (RechtJiva, 2026)
This research is motivated by the existence of normative ambiguity in Article 82 paragraph (1) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), particularly regarding the measure of returning a child to parental custody, which is not accompanied by clear mechanisms for guidance, supervision, and legal obligations. This condition has resulted in inconsistencies in the imposition of sanction measures on child offenders of sexual violence crimes in judicial practice. This study aims to analyze the basis of judges’ considerations in imposing criminal penalties and measures in several juvenile court decisions, to examine the strengths and weaknesses of the types of sanction measures regulated under the UU SPPA, and to assess the relevance of the parenting order model in England as an alternative for strengthening sanction measures within the juvenile criminal justice system in Indonesia. The research employs a normative juridical method with statutory, case, conceptual, and comparative approaches. The primary legal materials consist of statutory regulations and court decisions, while the secondary legal materials include legal literature and academic journals. The results indicate that differences in the imposition of criminal penalties and measures are influenced by variations in judges’ interpretations of the age of criminal responsibility, the objectives of punishment, and the absence of clear guidelines in the application of sanction measures. Furthermore, the measure of returning a child to parental custody has fundamental weaknesses due to the lack of enforceable obligations and measurable supervision mechanisms. Therefore, the parenting order model in England is considered applicable as an alternative for strengthening sanction measures in order to enhance the effectiveness of child rehabilitation and prevent the recurrence of criminal behavior.